Enhancing metal 3D printing with fused deposition modeling - a short review - Iftekar, Syed Fouzan; Sukindar, Nor Aiman; Amir, Adibah; Azami, Muhammad Hanafi; Aabid, Abdul (IJPUBLICATION, 2023)
Nowadays, additive manufacturing technology has many uses and has reached to incredible heights, but when it comes to 3D printing Metal, problems arise. Small organizations & businesses cannot even afford the costs associated with such specialized equipment since 3D printing in metal especially the SLM & EBM methods, is so expensive. Researchers have developed a novel way of 3D printing metal using Fused Deposition Modeling (FDM) techniques to solve this problem. This article gives a short analysis of Metal 3D printing using the Fused Deposition Modeling technique.